History of poliomyelitis: from elimination to the risk of reintroduction (Research, Society and Development, 2023)
Immunization is validated as one of the most successful and tangible actions, which actually result in the control and eradication of numerous pathologies across the planet. Despite this, the decrease in the vaccination coverage rate in Brazil and in the world is quite worrying, and may lead to the reintroduction of diseases that were previously controlled and eliminated. In view of this, with the objective of carrying out an analysis of the situation of the different regions of the earth, considering their disparities, the current work highlights areas with a reduction in the rate of vaccination coverage against poliomyelitis since 2016. An integrative review of literature, searching articles published between the years 2018 to 2022, in Spanish, English and Portuguese. The results observed in the 20 articles showed that Afghanistan and Pakistan are the only countries that are not polio free. In addition, the COVID-19 pandemic helped to accentuate the reduction in the vaccination rate in Brazil and in the world. With this, the decrease in vaccination coverage evidenced since 2016 confirms the relevance of this study, highlighting the importance of having a greater degree of understanding on the subject, in addition to more effective actions to increase vaccination coverage, such as public health campaigns.